Impact of Rice Production, Rice Supply And Rice Prices on Food Security in North Timor District - Be, Emanuel (School of Business, Bogor Agricultural University (SB-IPB), 2022)
This research was conducted in North Central Timor District, with the aim of analyzing food security by making the variables of rice production, rice supply, and rice prices as indicators that have an impact on food security. The analytical approach used is quantitative analysis with the ordinary least square. The results of the research analysis show that rice production has a positive and significant effect on food security. The availability of rice affects food security. Meanwhile, the price of rice has no effect on food security. Rice is a basic need so that when there is a price change it does not affect food security in the community. From the results of this study, it is hoped that the local government will carry out an extensification and diversification program for agricultural land so that there will be more and more variety in preparing food security for the people as well as adding knowledge and references for writers related to food security for the people of North Central Timor. Keywords: rice production, rice availability, rice prices, food security